Microalgae: A renewable source for wastewater treatment and feedstock supply for biofuel generation - Mustafa H.M.; Hayder G.; Jagaba A.H. (AMG Transcend Association, 2023)
The search and exploitation of renewable clean energy sources have become crucial, because of the developing day by day interest for clean water and energy affected by the improvement of the economy, population, industrialization, urbanization, insufficient energy, climate abnormalities, and environmental pollution. The major cause of emissions of harmful gases into the environment is due to the high utilization of petroleum derivatives. In this way, it is paramount to explore environmentally sustainable energy sources for feasible advancement, to satisfy these expanding energy demands and to secure the environment. To mitigate these global problems, academic, industrial, and governmental sectors have engaged in a lot of brainstorming and research to surmount these difficulties, which have brought a steady flow of new information in the area of cultivation of microalgae in innovative technologies including photobioreactors and high rate algal ponds. In this respect, biomass generation from aquatic plants in enriched aquatic environments like wastewater has received considerable. Therefore, this review article provides comprehensive information on recent accounts on applications of microalgae in wastewater treatment using different technologies and their potentials in feedstock generation for biofuels applications. However, in the course of this study, high rate algal ponds (HRAP) and photobioreactors were found to be a reliable system for the cultivation of microalgae and wastewater treatment. Hence, the two-step method of dewatering methods is found to be the most effective approach for microalgae cultivation for wastewater treatment and generation of algal-based feedstock, taking into account high yield potentials and economic factors such as cost of operation and energy required for large scale algal biomass processing for biofuel generations. AMG Transcend Association. All rights reserved.